Perubahan Iklim Formasi Sentolo pada Kala Miosen Awal - Pliosen di Jalur Kali Serang, Nanggulan, Kulon Progo - Alansyah, Apriko Yudhan; Nadhip, Muhammad; Erlandi, Muhammad; Kurniawan, Sandi; Rizqi, Al Hussein Flowers; Subandini Astuti, Bernadeta; Supandi, Supandi (Retii, 2023)
The research area is included in the Physiography of the Kulon Progo Mountains to the south, in Kali Serang, Kec. Nanggulan, Kulon Progo Regency, Special Region of Yogyakarta. This study aims to determine the pattern of ancient climate change in the middle Sentolo formation, which is used to correlate the ancient climate in the upper Sentolo formation to previous researchers. The results of the field data obtained at the study site were two facies, packstone and grainstone, which are included in the bioclastic limestone unit with a thickness of 30m. Identifying microfossils with samples (top, middle, bottom) obtained several species of benthonic foraminifera fossils totaling 89 and 79 planktonic foraminifera. The results of calculating the relative ages of the Sentolo formation in this study ranged from N13-N14 (middle Miocene). Based on the calculation of the p/b ratio for determining the depositional environment is in the middle neritik - outer neritik. In calculating the percentage of fossils that characterize warm temperatures (Globigerinoides spp., Orbuliniforms, Globorotalia menardi, Globorotalia praemenadri, Globigerina venezuelana, Globoquadrina dehiscens, Globoquadrina praedehiscens, Globigerinella obesa, Globorotalia siakensis) and cold (Catapsydrax, globigerina woodi, Globorotalia scitula, Globigerrina sp p.s., Globorotaloides). Entering the outer neritic depositional environment, the climate gradually cools down, marked by an increasing number of fossils characteristic of cold temperatures. Determination of changes in ancient climate patterns at the research blood location using an analysis of the abundance of planktonic foraminifera that characterizes warm and cold temperatures in the study area has one pattern of temperature change, namely the cooling phase. The cooling phase begins at N13 - N14, and the temperature gets colder with deeper ocean depths occurring in the study area in the middle-outer neritic depositional environment. Keyword : Foraminifera, Ancient Climate, Sentolo Formation